National treasure the tresure hunter's collection ([California] : Walt Disney Pictures, 2008)
National Treasure:With the help of museum curator Dr Abigail Chase and pursued by the FBI led by an investigator named Sadusky as well as Howe and his henchmen, treasure hunter Benjamin Franklin Gates becomes caught up in a desperate race against time to decipher the clues and unlock a 2,000-year-old mystery!
National Treasure 2 - Book of Secrets:In this follow-up to the box office hit National Treasure, treasure hunter Ben Gates must clear his family name after his great-great grandfather is implicated as a key conspirator in Abraham Lincoln's death!
National treasure - National treasure 2: book of secrets
Title from container
Bonus features: On Location, deleted Scenes, opening scene animaticalternate ending, treasure hunters revealed, riley Poole's decode this!the templar knights, trivia track viewing mode
DVD Format
Dolby digital
With optional English, Chinese, Korean, Indonesian, Thai or Malay subtitles
Keywords: Treasure troves -- Drama; Lost articles -- Drama